Savremeni sigurnosni izazovi kao faktor modeliranja nove sigurnosne politike Bosne i Hercegovine / Contemporary Security issues as Factor of Redefinitions of National Security Strategy of Bosnia and Herzegovina - Planinčić, Amila (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Since the end of the armed conflict on its territory, the political system of Bosnia and Herzegovina (BiH) has been going through a very complex post-conflict development of its civilian and security structures. Since 1995 Bosnia and Herzegovina had a political reform process that required implementation of the security sector reform as well. According to numerous authors, reform of defense system has been one of the best implemented in so-called “post-conflict Bosnia and Herzegovina.“ One of the highpoints of the aforementioned reform was drafting and adoption of Security Strategy of BiH in 2006. The peculiarities of this document lies in the socio-political era during which it had been created, and it sets down the fundamental strategic directions and guidelines about the organization of the national security system of Bosnia and Herzegovina. Apart from defining aims and tasks in domain of national security, this document underlines local, regional and global security challenges that could endanger or inhibit independency, sovereignty or stability of BiH. Considering the fact that since the period Security Strategy of BiH was adopted, many security challenges appeared on global, regional and local level, it is indispensable to reconsider the necessity for Security Strategy update, so it could be effective and in accordance with the changed security environment. The present work aims to present the relation between the emerging security issues from national to global level and the current Security Strategy of BiH, as well as to emphasize those security issues that act as a key factor of redefinition of the current Security Strategy of BiH.